Desenvolvimento de métodos analíticos empregando a espectrometria de absorção atômica sequencial rápida com atomização em chama - Miranda, Kelber dos Anjos de (Universidade Federal de São Carlos, 2012)
The aim of this PhD thesis was to develop analytical methods employing fast sequential flame atomic absorption spectrometry (FS-FAAS). In the first part of this study, a fast and simple method is proposed for the determination of Cu in sugar cane spirits employing FS-FAAS and the internal standard technique. First, Ag, Bi, Co and Ni were evaluated as internal standards to correct transport interferences caused by the presence of ethanol. The results demonstrated that Ag at a concentration of 2 mg L−1 was effective as internal standard. In the second part of this study, a novel analytical method which consists of a combination of hydride generation and FS-FAAS is proposed. The method developed was employed for the sequential determination of As and Sb at sub-μg L-1 levels in bottled mineral waters. An enhancement in the analytical throughput was obtained when compared with the traditional monoelement HGAAS with a quartz tube atomizer. In the last part of the study, the combination of thermospray flame furnace atomic absorption spectrometry (TS-FF-AAS) and FS-FAAS for the sequential determination of Cd, Cu, Pb and Zn was proposed and a significant improvement in the analytical throughput of TS-FFAAS was obtained. Then, an analytical method for the sequential determination of Cd, Cu and Pb in slurries of biological samples by TS-FF-AAS was developed.
Development of analytical methods employing fast sequential atomic absorption spectrometry with flame atomization
Keywords: Espectroscopia de absorção atômica; FS-FAAS; TS-FF-AAS; HGAAS; CIENCIAS EXATAS E DA TERRA::QUIMICA